Mid-radiotherapy PET/CT for prognostication and detection of early progression in patients with stage III non-small cell lung cancer. Issue 2 (November 2017) - Gensheimer, Michael F.; Hong, Julian C.; Chang-Halpenny, Christine; Zhu, Hui; Eclov, Neville C.W.; To, Jacqueline; Murphy, James D.; Wakelee, Heather A.; Neal, Joel W.; Le, Quynh-Thu; Hara, Wendy Y.; Quon, Andrew; et al.
Abstract: Background and purpose: Pre- and mid-radiotherapy FDG-PET metrics have been proposed as biomarkers of recurrence and survival in patients treated for stage III non-small cell lung cancer. We evaluated these metrics in patients treated with definitive radiation therapy (RT). We also evaluated outcomes after progression on mid-radiotherapy PET/CT. Material and methods: Seventy-seven patients treated with RT with or without chemotherapy were included in this retrospective study. Primary tumor and involved nodes were delineated. PET metrics included metabolic tumor volume (MTV), total lesion glycolysis (TLG), and SUVmax . For mid-radiotherapy PET, both absolute value of these metrics and percentage decrease were analyzed. The influence of PET metrics on time to death, local recurrence, and regional/distant recurrence was assessed using Cox regression. Results: 91% of patients had concurrent chemotherapy. Median follow-up was 14 months. None of the PET metrics were associated with overall survival. Several were positively associated with local recurrence: pre-radiotherapy MTV, and mid-radiotherapy MTV and TLG ( p  = 0.03–0.05). Ratio of mid- to pre-treatment SUVmax was associated with regional/distant recurrence ( p  = 0.02). 5/77 mid-radiotherapy scans showed early out-of-field progression. All of these patients died. Conclusions: Several PET metrics were associated with risk of recurrence. Progression on mid-radiotherapy PET/CT was a poor prognostic factor.